Benin - Enhancing the Effectiveness of Public Spending : A Review of Three Sectors - World Bank (Washington, DC, 2013)
This public expenditure review, the first since 1997, focuses on selective themes and sectors and is written as part of the Poverty Reduction Support Credit (PRSC) cycle. The first PRSC focused on policies and reforms having maximum impact on poverty with the aim of 1) maintaining macroeconomic stability and promoting growth; 2) strengthening public expenditure management reform; 3) improving PRESTATION lending the quality and widening coverage of public service delivery while strengthening the effectiveness of public spending in these sectors; and 4) financing the government spending program in key sectors. This report addresses three themes: 1) the development of the public expenditure program; 2) the outcomes of public spending in the health, education, and rural water sectors; and 3) the review of the reform agenda for managing public expenditures.